Practices regarding human Papillomavirus counseling and vaccination in head and neck cancer: a Canadian physician questionnaire - Scott Anderson; Andre Isaac; Caroline C. Jeffery; Joan L. Robinson; Daniela Migliarese Isaac; Christina Korownyk; Vincent L. Biron; Hadi Seikaly (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Human papillomavirus (HPV) has recently been implicated as a causative agent in a rapidly growing number of oropharyngeal cancers. Emerging literature supports the hypothesis that HPV vaccination may protect against HPV-related head and neck cancer (HNC) in addition to HPV-related cervical and anogenital disease. While the association between HPV infection and cervical cancer is widely understood, its relation to HNC is less well known. The purpose of this study was to better understand HPV counseling practices for infection and vaccination in relation to HNC of primary care physicians (PCPs), Obstetricians/Gynecologists (OBGYNs), and Otolaryngology - Head and Neck Surgeons (OHNSs) in Canada. Methods A Canada-wide electronic questionnaire regarding counseling practices on HPV infection, transmission, and vaccination was designed and distributed to PCPs, OBGYNs, and OHNSs across Canada through electronic and paper-based methods. Basic Descriptive statistics were used to analyze responses. Results In total, 337 physicians responded (239 family physicians, 51 OHNSs, 30 OBGYNs, and 17 pediatricians). Three out of four PCPs reported routine counseling of their patients regarding HPV infection, transmission, and vaccination. Among this group, 68% reported “never” or “rarely” counseling patients that HPV can cause HNC. The most commonly reported reason that PCPs cited for not counseling was a lack of knowledge. The majority of OHNSs (81%) and OBGYNs (97%) counseled patients regarding HPV infection, transmission, and vaccination. However, very few OHNSs (10%) regularly counseled patients with HPV-related HNC about HPV-related anogenital cancer. Similarly, very few OBGYNs (18%) regularly counseled patients with HPV related cervical/anogenital cancer about HPV related HNC. Conclusions The rate of counseling on HPV infection, transmission, and vaccination in relation to HNC among PCPs is low. The most common reason is a lack of knowledge. Specialists rarely counsel patients with confirmed HPV-related cancer about other HPV-related malignancies. More research is needed on the relationship between different HPV-related cancers in order to better inform counseling practices.